2010
DOI: 10.1673/031.010.10101
|View full text |Cite
|
Sign up to set email alerts
|

Facultative Hyperparasitism: Extreme Survival Behaviour of the Primary Solitary Ectoparasitoid,Dinarmus basalis

Abstract: This study investigated the egg-laying behaviour of ectoparsitoid, Dinarmus basalis Rondani (Hymenoptera: Pteromalidae), females when faced with a prolonged deprivation of suitable hosts leading to extreme ‘oviposition pressure’. The egg-laying behaviour of virgin D. basalis females was tested with Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) hosts previously parasitized by the conspecific females in which the developing larvae had reached the last larval instar (L5) or pupae. The hyperparasitism did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This research has confirmed reports by Ketoh et al (2002), Iloba et al (2007), Rojas-Rousse (2010) that Dinarmus basalis and Choetospila elegans reduce the population of bruchids in stores and therefore has the potential for utilization as a biological control agent against a serious internal-feeding pest of small grains, C. maculatus in a traditional storage bin. The time of introduction of the parasitoid wasps was very crucial in arresting the vulnerable stages of the bruchids which are the larval, the pre-pupa and the pupal stages.…”
Section: Discussionsupporting
confidence: 89%
“…This research has confirmed reports by Ketoh et al (2002), Iloba et al (2007), Rojas-Rousse (2010) that Dinarmus basalis and Choetospila elegans reduce the population of bruchids in stores and therefore has the potential for utilization as a biological control agent against a serious internal-feeding pest of small grains, C. maculatus in a traditional storage bin. The time of introduction of the parasitoid wasps was very crucial in arresting the vulnerable stages of the bruchids which are the larval, the pre-pupa and the pupal stages.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, T. japonicus engages in more aggressive interactions and spends more time foraging on guarded (already‐parasitized) egg masses despite the fact that oviposition is rarely successful and developmental outcome is poor. However, this may be an artefact of increased oviposition pressure in no‐choice tests or small‐cage arenas (Murray et al, 2010 ; Rojas‐Rousse, 2010 ), or it may be due to a high egg load or low egg retention capacity in the absence of suitable hosts (Agboka et al, 2002 ; Collier et al, 2002 ; Stokkebo & Hardy, 2000 ). Choice tests in future studies may help clarify whether T. japonicus is able to discriminate between suitable (unparasitized) and unsuitable (parasitized) host eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Dinarmus basalis (Pteromalidae) can also lay eggs on hosts containing conspecific larvae or pupae, but very few D . basalis eggs from hyperparasitized conspecific old larvae reach the adult stage [ 38 ]. Also, some smaller offspring had been observed when D .…”
Section: Discussionmentioning
confidence: 99%
“…Also, some smaller offspring had been observed when D . basalis secondarily parasitized hosts, which was taken as a result of superparasitism and the depletion of host resources [ 38 ]. Whether these reports can be classified as conspecific hyperparasitism behavior needs further research.…”
Section: Discussionmentioning
confidence: 99%